2015
DOI: 10.4081/pr.2015.5955
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Noonan Syndrome RAF1 Mutation: Lethal Course in a Preterm Infant

Abstract: Noonan syndrome is a relatively common and heterogeneous genetic disorder, associated with congenital heart defect in about 50% of the cases. If the defect is not severe, life expectancy is normal. We report a case of Noonan syndrome in a preterm infant with hypertrophic cardiomyopathy and lethal outcome associated to acute respiratory distress syndrome caused by Adenovirus pneumonia. A novel mutation in the RAF1 gene was identified: c.782C>G (p.Pro261Arg) in heterozygosity, not described previously in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…However, recent genetic and molecular studies have demonstrated that most cardiomyopathy cases have genetic defects and some are inheritable [23]. So far, the common disease genes for HCM have been summarized as those of MYH7 , MYH6 , TPM1 and RAF1 [2427]. In our study, we also identified that MYH7 mutation is one of the most common gene variants in HCM cases.…”
Section: Discussionsupporting
confidence: 66%
“…However, recent genetic and molecular studies have demonstrated that most cardiomyopathy cases have genetic defects and some are inheritable [23]. So far, the common disease genes for HCM have been summarized as those of MYH7 , MYH6 , TPM1 and RAF1 [2427]. In our study, we also identified that MYH7 mutation is one of the most common gene variants in HCM cases.…”
Section: Discussionsupporting
confidence: 66%
“…A total of 79.2% of pathogenic RAF1 alleles affect residues within the 14‐3‐3ζ recognition site of CR2, such as Arg256, Ser257, Ser259, Thr260, Pro261, Asn262, and Val263 (Kobayashi et al, ; Pandit et al, ; Razzaque et al, ; Sana et al, ); binding of RAF1 to 14‐3‐3ζ is critical for its autoinhibition (Kubicek et al, ; Light, Paterson, & Marais, ). The second group of mutations (8.1%) affects the adjacent residues Ser612 and Leu613 located C‐terminally to the CR3 domain, and the third group (7.9%) affects the two amino acid residues Asp486 and Thr491 within the activation segment of the kinase domain (Croonen et al, ; Hartill, Dillon, Warren, & Blyth, ; Hopper, Feinstein, Manning, Benitz, & Hudgins, ; Ko, Kim, Kim, & Yoo, ; Kobayashi et al, ; Pandit et al, ; Ratola et al, ; Razzaque et al, ; Sana et al, ; Schulz, Frober, Kraus, & Schneider, ). Only two amino acid substitutions in CR3 have been described so far (4%): p.(Ser427Gly) was found in mother and son with NS as well as in an unrelated patient (Kobayashi et al, ; Zebisch et al, ), and p.(Glu478Lys) was found in one patient (Ezquieta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, RAF1 is often implicated in Noonan syndrome cases diagnosed prenatally, in the first several weeks after birth, or on fetal autopsy. [57910] The trend in earlier diagnosis could point toward RAF1 mutations being either more severe or more clinically apparent than other forms of Noonan syndrome. Furthermore, mortality rate has been documented to be higher among this same set.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mortality rate has been documented to be higher among this same set. [5710] Kobayashi et al have suggested that the remarkably higher incidence of heart conditions—including hypertrophic cardiomyopathy and biventricular hypertrophy—is likely responsible for this finding. [7]…”
Section: Discussionmentioning
confidence: 99%